Free Market Fairness - Tomasi, John, 1961- (Book collections on Project MUSE., 2012)
Can libertarians care about social justice? In Free Market Fairness, John Tomasi argues that they can and should. Drawing simultaneously on moral insights from defenders of economic liberty such as F.A. Hayek and advocates of social justice such as John Rawls, Tomasi presents a new theory of liberal justice. This theory, free market fairness, is committed to both limited government and the material betterment of the poor. Unlike traditional libertarians, Tomasi argues that property rights are best defended not in terms of self-ownership or economic efficiency but as requirements of democratic legitimacy.